From juvenile delinquency to adult crime : criminal careers, justice policy and prevention - Loeber, Rolf.; Farrington, David P. (New York ; Oxford : Oxford University Press, 2012)
What makes a juvenile delinquent develop into an adult criminal? Edited by two leading authorities in the fields of psychology and criminology, this title examines why the period of transition to adulthood is important and how it can be better understood and addressed both inside and outside of the justice system.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on July 9, 2012).
Keywords: Juvenile delinquency; Juvenile delinquency -- Prevention; Criminal behavior, Prediction of; Criminal justice, Administration of